The Impact of a Passive Portfolio Management Strategy on Portfolio Return and Risk - A. Mahmood, Ahmed (Accounting Department,, 2025)
Purpose — This study aims to address issues in the preparation of passive investment portfolios using stocks listed on the Iraq Stock Exchange. The main focus is to build a common stock portfolio that can achieve the best trade-off between return and risk, adjusted to the preferences and risk tolerance of investors in the financial market. Design/methodology/approach — This study uses an explanatory quantitative approach by applying the fuzzy time series method to handle ambiguity and volatility in the monthly closing price data of eight banks listed on the Iraqi Stock Exchange during the period 2012–2021. The analysis was conducted by comparing the performance of the passive investment portfolio against the market portfolio performance. Findings — The results show that passive investment portfolios with high beta values (βpt) outperform other portfolios because they achieve an optimal balance between return and risk. However, it was found that bank stock returns are highly sensitive to market movements, and their performance was limited by sectoral concentration and inefficiencies in bank management. Practical implications — Investors in the Iraqi capital market are advised to adopt modern portfolio formation models and prioritize high-beta strategies, while still considering other factors such as company size, profitability, and liquidity to diversify risk. In addition, financial analysts and brokers are encouraged to expand passive portfolio models to sectors other than banking. Originality/value — This article presents a comprehensive algorithm for the passive portfolio formation process in the context of the Iraqi capital market, which has specific challenges in the form of an unstable environment and limited financial instruments. The use of fuzzy time series in this study contributes to the literature on estimation methods in emerging markets.